Mechanistic Insights into LGALS3-Mediated Osteoarthritis Progression: Activation of the cGAS-STING Pathway as a Key Driver of Senescence-Related Osteoarthritis - Ruolan Wu; Tong Xiao; Zhen Chen; Qitao Yan; Ying Wang; Dingwei Peng; Jingli Chen; Ge Zeng (Journal of Pharmaceutical Innovation, 2026)

Multi-media antibiotics, intracellular and extracellular antibiotic resistance genes in marine protected areas of the South China Sea: Spatiotemporal distribution and multi-factor drivers of dissemination - Chengcheng Bu; Limin Ma; Yu Hua; Shaopeng Xu; Yutong Zhang; Huadong Yi; Yuchen Han; Haoyu Zeng; Yongzhi Wang; Xiaoying Xu; Qihui Zhao; Ruolan Jia; et al. (Marine Pollution Bulletin, 2026)

Spatiotemporal dynamics and spatial attribution of water conservation under land use/cover changes and the SSP2–4.5 medium-forcing scenario in the northern slope of the Tianshan Mountains - Hongjie Jia; Qin Han; Yingchao Ji; Dong Liu; Ruolan Chen; Jiangyue Li; Haoyang Du (Regional Environmental Change, 2026)

The impact of the construction of national key ecological function zones on county-level ecological resilience - Chao Chen; Ruolan Yuan; Yang Liu; Feng Ye; Wenmei Liao (Environment, Development and Sustainability, 2026)

PMS activation by MOF-derived bimetallic Mn0.8Co2.2O4 spinel: Efficient ofloxacin mineralization and synergistic mechanism elucidation - Sijie Ge; Ge Chen; Zhaochang Wu; Mengchen Zong; Ruolan Chen; Jie Zhang (Chemical Engineering Journal, 2026)

Multi-media distribution, source apportionment, and risk assessment of legacy and current-use organophosphorus pesticides in typical agricultural watersheds of China - Chengcheng Bu; Limin Ma; Weiwei Zhang; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Qi Wang; Yuefei Ruan; Chong Chen (Water Research, 2026)

Occurrence and differential spatiotemporal distribution of pesticides in a plateau lake basin with intensive vegetable cultivation: A case study in Qilu Lake Basin - Qihui Zhao; Limin Ma; Chengcheng Bu; Yu Hua; Ruolan Jia; Chong Chen (Environmental Research, 2026)

RSAND: A Fine-Grained Dataset and Benchmark for AtoN Detection in River–Sea Intermodal and Complex Estuarine Environments - Qi Chen; Mingyang Pan; Zongying Liu; Ruolan Zhang; Fei Yan; Xiaofeng Pan; Yang Zhang; Chao Li (Journal of Marine Science and Engineering, 2026)
Robust visual perception of Aids to Navigation (AtoN) is essential for Maritime Autonomous Surface Ships (MASS) operating in restricted navigational waters, where estuarine clutter, fog, glare, and dense traffic can severely degrade detection reliability. Existing maritime vision datasets largely emphasize open-sea targets or coarse AtoN categories, leaving a granularity gap for IALA-compliant fine-grained understanding in river–sea transition and port-approach channels. The River–Sea AtoN Navigation Dataset (RSAND) is introduced, a large-scale benchmark collected along the Yangtze River Deepwater Channel from inland corridors to open estuarine waters. RSAND contains 39,926 images with expert-verified bounding-box annotations and a hierarchical taxonomy that jointly captures AtoN location, shape, and functional semantics across 29 categories. To support both realistic long-tailed evaluation and standardized model comparison, two protocols are provided: RSAND-Full (29 categories) and RSAND-Balanced (10 critical categories). All quantitative benchmarking results in this paper are reported on RSAND-Balanced, while RSAND-Full is released for future large-scale long-tailed robustness studies. Benchmarking experiments on 14 state-of-the-art detectors demonstrate that YOLOv12x achieves superior performance with an mAP50-95 of 80.7%, significantly outperforming previous baselines. However, the analysis reveals persistent challenges in detecting small, distant targets and distinguishing visually similar functional markers. RSAND and the accompanying evaluation toolkit are released to facilitate reproducible research toward safer and smarter marine and coastal navigation.

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

Al-doped Ti4O7 with superior oxidation resistance and optical stability for high-temperature solar-thermal applications - Peize Lyu; Wenzhao Sun; Bo Yang; Wanqi Chen; Ruolan Tang; Haile Yan; Zongbin Li; Song Li; Liang Zuo (Chemical Engineering Journal, 2026)

Stratified layering for soil profile: Dynamic short field Mamba network - Shaohua Zeng; Zhihao Chen; Ruolan Zeng; Shuai Wang; Yang Wang (Computers and Electronics in Agriculture, 2026)

Mechanistic differences in ce-MoS2 catalytic activation of peroxides: Pathway divergence and reactive species roles - Shuyun Tai; Lei Sun; Yuxin Wang; Ruolan Huang; Yang Yang; Yu Chen; Hong Chang (Journal of Hazardous Materials, 2025)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Hierarchical sulfur vacancy engineering via lattice strain for commercial-grade photocatalytic H2O2 generation in Sm3+-doped ZnIn2S4 - Ruolan Zhao; Chen Chen; Yachao Xu; Yue Qu; Peng Yu; Ying Wang (Chemical Engineering Journal, 2025)

Tidal channel morphology controls on water exchange and sedimentation Patterns: Implications for sustainable reclamation design in semi-enclosed lagoons - Ruolan Yu; Chen Zhang; Zixuan Zhu; Yinzhu Liu (Marine Environmental Research, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Spatial distribution, phase partitioning, and ecological risk assessment of typical pesticides in Yangtze River Basin - Chengcheng Bu; Chong Chen; Xitong Fu; Weiwei Zhang; Ru Zhang; Yu Hua; Ruolan Jia; Yuefei Ruan; Kenneth Mei Yee Leung; Limin Ma (Journal of Hazardous Materials, 2025)

A reversible fluorescence probe enables bioimaging and toxicity evaluation of lithium ion in living human cells - Cheng Gong; Peiming Zhang; Ya Liu; Ruolan Chen; Kai Huang; Weizhun Yang; Lirong Gao; Ming Xu; Xuezhi Yang; Yin Liu; Qian Liu; Bing Yan; et al. (Journal of Hazardous Materials, 2025)

The effect of probiotics supplementation on cancer-treatment complications: a critical umbrella review of interventional meta-analyses - Zhao Yang; Shijie Zhang; Lu Ying; Wenjing Zhang; Xiaoyang Chen; Youfeng Liang; Ruolan Chen; Keying Yao; Chunhui Li; Changyuan Yu; Parmida Jamilian; Meysam Zarezadeh; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Bioremediation potential of sulfadiazine-degrading bacteria: Impacts on ryegrass growth and soil functionality - Minghao Yin; Ping Li; Chengzhuang Chen; Ruolan Jia; Banghua Xia; Yiwei Liu; Aiqiu Liu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

SQSTM1/p62 predicts prognosis and upregulates the transcription of CCND1 to promote proliferation in mantle cell lymphoma - Shuxia Zhang; Feichao Huang; Jin Wang; Ruolan You; Qiqi Huang; Yuanzhong Chen (Protoplasma, 2025)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Interaction of high amylose corn starch with polyphenols: Modulating the stability of polyphenols with different structure against thermal processing - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Chemistry, 2024)

Study on the improvement of complexation efficiency and anti-digestibility of phenolic acids based on electrospun starch fibers - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yanhong Bi; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2024)

Chemometrics-based investigation of non-volatiles/volatiles flavor of tencha (Camellia sinensis cv. Yabukita, Longjing 43 and Baiye 1) - Qiuwen Yu; Chuangsheng Huang; Ruolan Zhu; Debiao Lu; Liping Liu; Jianhong Lai; Xinyao Zhong; Jueshan Guan; Senjie Zhou; Yilin Tong; Zipei Wang; Ping Chen; et al. (Food Research International, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Stagnant water environmental management in urban river networks: An integrated risk analysis involving hydraulic potential dissipation - Ruolan Yu; Chen Zhang; Xueping Gao; Kensey Daly (Journal of Hydrology, 2023)

Shellfish-algal systems as important components of fisheries carbon sinks: Their contribution and response to climate change - Ruolan Jia; Ping Li; Chengzhuang Chen; Ling Liu; Zhi-Hua Li (Environmental Research, 2023)

Effects of radon exposure on gut microbiota and its metabolites short-chain fatty acids in mice - Huimeng Liu; Meiyu Wang; Guangrui Chen; Huiyu Zhou; Jiahui Dong; Lei Yang; Tong Li; Zhiyun Meng; Ruolan Gu; Hui Gan; Zhuona Wu; Shuchen Liu; et al. (Toxicology, 2023)

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

A novel antibacterial tyroscherin derivative with a natural unprecedented morpholine-2, 3-dione structural unit from the fungus Pseudallescheria boydii - Ruolan Chen; Ziyang Li; Chan Qin; Peijun Lu; Jiaru Lin; Wenxu Zheng; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

Optimisation of regeneration parameters improves transformation efficiency of recalcitrant tomato - Cahya Prihatna; Ruolan Chen; Martin John Barbetti; Susan Jane Barker (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)